Conformational heterogeneity of the Pfr chromophore in plant and cyanobacterial phytochromes - Velazquez Escobar, Francisco; von Stetten, David; Günther-Lütkens, Mina; Keidel, Anke; Michael, Norbert; Lamparter, Tilman; Essen, Lars-Oliver; Hughes, Jon; Gärtner, Wolfgang; Yang, Yang; Heyne, Karsten; Mroginski, Maria Andrea; et al. (Frontiers in Molecular Biosciences, 2015)
Phytochromes are biological photoreceptors that can be reversibly photoconverted between a dark and photoactivated state. The underlying reaction sequences are initiated by the photoisomerisation of the tetrapyrrole cofactor, which in plant and cyanobacterial phytochromes are a phytochromobilin (PB) and a phycocyanobilin (PCB), respectively. The transition between the two states represents an on/off-switch of the output module activating or deactivating downstream physiological processes. In addition, the photoactivated state, i.e. Pfr in canonical phytochromes, can be thermally reverted to the dark state (Pr). The present study aimed to improve our understanding of the specific reactivity of various PB- and PCB-binding phytochromes in the Pfr state by analyzing the cofactor structure by vibrational spectroscopic techniques. Resonance Raman (RR) spectroscopy revealed two Pfr conformers (Pfr-I and Pfr-II) forming a temperature-dependent conformational equilibrium. The two sub-states - found in all phytochromes studied, albeit with different relative contributions - differ in structural details of the C-D and A-B methine bridges. In the Pfr-I sub-state the torsion between the rings C and D is larger by ca. 10o compared to Pfr-II. This structural difference is presumably related to different hydrogen bonding interactions of ring D as revealed by time-resolved IR spectroscopic studies of the cyanobacterial phytochrome Cph1. The transitions between the two sub-states are evidently too fast (i.e., nanosecond time scale) to be resolved by NMR spectroscopy which could not detect a structural heterogeneity of the chromophore in Pfr. The implications of the present findings for the dark reversion of the Pfr state are discussed.